Road accident analysis factors - Esmaeeli, Hamed (2010)
The problem of road accident is increasing in developing countries. A matter of research has been and is being committed to this topic, as a search of past and current research shows. Road accidents in developing countries have progressed over the last ten years. This could be because of increasing vehicle occupancy over time or to the fact that a particular type of accident is much more common now than was the case ten years ago. For instance commercial vehicles are currently used to transport workers to and from their places of their work. When such a vehicle is involved in an accident, large numbers of mortalities often occur. This report investigates the modelling and implementation of a coordination system within a simulation environment to foresee future accident rate. The approach of analysis used must be correspondingly robust and objective to evaluate accident rate. To comparing changes in car ownership, we hope to use these data to investigate the factors behind these changes. Some examples are the effect of income, changes in employment, changing household structure and changes in residential and work location. They should not be too sensitive to departures from model assumptions or the presence of a substantial number of outliers. Given the polluted nature of the data, ordinary least squares regression is not suitable, therefore, robust regression techniques are recommended.